Analisis Kemampuan Literasi Matematika dan Numerasi Ditinjau dari Gaya Kognitif Siswa pada Materi Bilangan Bulat - Iqbal, Muhammad Adam; Jamilah, Jamilah; Risalah, Dewi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to find out the results of literacy and numeracy skills reviewed from students' cognitive styles. This study uses qualitative research methods. The form of this research is a case study. This research was carried out at SMP Negeri 13 Pontianak. The subjects of this study are students in grade VII F who have studied integer material. The subjects to be interviewed consisted of 4 students based on the categories of Field Independent and Field Dependent cognitive styles. The subject of this study was determined using a purposive sampling technique. The instruments used in this study are the GEFT test, written test and interview guidelines. The data produced was analyzed in a qualitative descriptive manner. The results of the study showed that students with mathematical literacy and numeracy skills in the FD category were only able to achieve 2 indicators out of 3 indicators. This is because students with the FD category also tend to hesitate and easily give up in dealing with the problems they face, while with the FI category students are able to meet 3 indicators. This is because students with the FI category are always optimistic and do not give up easily in solving the problems they face.